Democratic backsliding, regional governance and foreign policymaking in Southeast Asia: ASEAN, Indonesia and the Philippines. Issue 1 (2nd January 2021) - Rüland, Jürgen
ABSTRACT: This article examines democratic backsliding in the spheres of regional cooperation and foreign policymaking in Southeast Asia. It argues that backsliding is limited because the space for the Association of Southeast Asian Nations (ASEAN) and its member states to promote democracy has always been strongly curtailed by ideational path dependencies. These include an autocratic type of regional corporatism and the ASEAN Way as the region's established repository of cooperation norms. While ASEAN has thus largely failed to become more inclusive, democracy promotion policies of the grouping's democratically most advanced member states, Indonesia and the Philippines, are more ambiguous. Despite eroding democratic practices at home, democracy is still a pillar of Indonesia's foreign policy. By contrast, in the Philippines, the incumbent Duterte presidency increasingly securitizes foreign policy, relegating democracy to a backseat.